2008
DOI: 10.3855/jidc.321
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polymerase chain reaction and conventional methods in detecting methicillin-resistant Staphylococcus aureus

Abstract: Background: Accurate and rapid detection of methicillin-resistant Staphylococcus aureus is very important in a clinical laboratory setting to avoid treatment failure. Conventional methods were compared against the gold standard polymerase chain reaction (PCR) technique to determine the best combination of the routine procedures. Methodology: Methicillin resistance was investigated in 416 clinical Staphylococcus aureus isolates by PCR, oxacillin agar screening (OAS), oxacillin disk diffusion (ODD) and cefoxitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…The oxacillin agar screen method has also been recommended for confirmation of suspected strains by the CLSI. The studies evaluating these tests have showed that they have acceptable performance; in general, sensitivity (94.1%-100%) and specificity (87.4%-100%) ranges of the oxacillin disk diffusion method, cefoxitin disk diffusion method, and oxacillin agar screen test in these studies were found to be similar to those found in our study [19][20][21]. In Baddour et al's study [22], the oxacillin agar screen and PBP2a latex agglutination methods were reported to be more sensitive than the oxacillin and cefoxitin disk diffusion methods, and cefoxitin disk diffusion was found to be the most specific method.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The oxacillin agar screen method has also been recommended for confirmation of suspected strains by the CLSI. The studies evaluating these tests have showed that they have acceptable performance; in general, sensitivity (94.1%-100%) and specificity (87.4%-100%) ranges of the oxacillin disk diffusion method, cefoxitin disk diffusion method, and oxacillin agar screen test in these studies were found to be similar to those found in our study [19][20][21]. In Baddour et al's study [22], the oxacillin agar screen and PBP2a latex agglutination methods were reported to be more sensitive than the oxacillin and cefoxitin disk diffusion methods, and cefoxitin disk diffusion was found to be the most specific method.…”
Section: Discussionsupporting
confidence: 86%
“…[19][20][21]24]. Compared with the chromogenic agar MRSA assay, PCR had sensitivity, specificity, and positive and negative predictive values of 100%, 98.6%, 95.8%, and 100%, respectively, and the mean PCR turnaround time was 14.5 hours [4].…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic susceptibility test revealed that 50 strains were resisted to oxacillin/cefoxitin. Further, methicillin resistance in staphylococci isolated from clinical samples by Rahbar was 53% in Tehran and 51% of MRSA were also reported in Turkey (26).…”
Section: Discussionmentioning
confidence: 90%
“…El cassette de cromosomas codificadores del gen mec produce una alteracio n en la proteí na codificadora, a su vez, de la resistencia a los betalactamicos, mediante la expresio n de una nueva proteí na con baja afinidad por la meticilina, denominada PBP2a (Penicillin binding protein 2a por sus siglas en ingle s) (3,(7)(8)(9)(10). Así , se produce una disminucio n en la afinidad a dichos antibio ticos, debido a que solo posee un dominio para la transpeptidacio n. Esta modifica los peptidoglicanos de la pared bacteriana (7,10,11).…”
Section: Introductionunclassified